2020
DOI: 10.1002/bem.22258
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Exogenous Electromagnetic Field on Bone Cells: A Review

Abstract: Osteoporosis, fractures, and other bone diseases or injuries represent serious health problems in modern society. A variety of treatments including drugs, surgeries, physical therapies, etc. have been used to prevent or delay the progression of these diseases/injuries with limited effects. Electromagnetic field (EMF) has been used to non-invasively treat bone diseases, such as fracture and osteoporosis, for many years. However, because a variety of cellular and molecular events can be affected by EMF with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 89 publications
(132 reference statements)
0
18
0
2
Order By: Relevance
“…Furthermore, activation of PI3K/Akt signaling in MSCs under PEMFs osteogenic induction has been reported. Zhang and colleagues described increased levels of phosphorylated Akt, phosphorylated GSK3β, and nuclear β-catenin, indicating the Akt/GSK3β/β-catenin axis is involved in osteogenic differentiation, following PEMF exposure [ 28 ]. The involvement of Akt has been reported also by Poh and colleagues, who demonstrated that after PEMFs exposure at selected parameters, the activation of Akt in adipose derived mesenchymal stem cells, leads to a significant upregulation of bone-specific genes [ 29 ].…”
Section: Pemfs Molecular Pathways On Bone Healingmentioning
confidence: 99%
“…Furthermore, activation of PI3K/Akt signaling in MSCs under PEMFs osteogenic induction has been reported. Zhang and colleagues described increased levels of phosphorylated Akt, phosphorylated GSK3β, and nuclear β-catenin, indicating the Akt/GSK3β/β-catenin axis is involved in osteogenic differentiation, following PEMF exposure [ 28 ]. The involvement of Akt has been reported also by Poh and colleagues, who demonstrated that after PEMFs exposure at selected parameters, the activation of Akt in adipose derived mesenchymal stem cells, leads to a significant upregulation of bone-specific genes [ 29 ].…”
Section: Pemfs Molecular Pathways On Bone Healingmentioning
confidence: 99%
“…Sensing of methanol, ethanol, acetone, and ammonia is reported in literature by HAP and measured by electrical properties 11‐15 . Sensing of 1000 ppm CO and CO 2 gases using Fe doped HAp thick films have been reported by Mene et al with 91% and 112% response at temperature 140°C and 155°C, respectively 10 . Anjum et.…”
Section: Introductionmentioning
confidence: 98%
“…Hydroxyapatite, collagen, and fluids are major components of bone. Selective use of dielectric and electric properties of HAp can play a very important role to improve (a) hydroxyapatite's bioactivity with electric poling (b) bone growth with electrical stimulation for bone grafts in spinal fusion (c) healing and repairing of bone fractures with electric field and (d) osteonecrosis and osteoarthritis treatment 5‐10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations